دراسة الكفاءة الاقتصادية لزراعة نبات الشفليرا في البيوت البلاستيكية في الساحل السوري (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تضمن, البحث دراسة واقع نباتات الزينة في البيوت البلاستيكية, وهذا النوع من الزراعة لم يلق الدعم اللازم من الدولة, على الرغم من أن الساحل السوري يصلح لزراعة هذه النباتات, حيث وصل عددها إلى حوالى 1115 بيتاً عام 2003م . إن هذه الزراعة تحقق أرباحاً كبيرة بالمقارنة مع زراعات أخرى نتيجة تسويق إنتاجها محلياً وتصدير الفائض للخارج . ولقد اخترنا من نباتات الزينة المزروعة في البيوت البلاستيكية نبات الشفليرا, وذلك لأنه لا يحتاج إلى خبرة كبيرة و فترة تربية قصيرة حتى يسوّق. ولقد أجرينا مقارنة الكفاءة الاقتصادية لهذا النبات, إذ شملت الدراسة ثلاث مراحل عمرية الأولى ستة أشهر, والثانية سنة واحدة, والثالثة سنة ونصف في صالة مساحتها حوالى 1000م2, وأخرى للأمهات, وحصلنا على نتائج مذهلة, فالتربية لمدة ستة أشهر حققت ربحاً سنوياً قُدِّر بحوالى238414 ل.س, والفترة الثانية 174674 ل.س, والثالثة 140045 ل.س, وهذه الأرقام تتحقق إذا توفرت الخدمات اللازمة والخبرة الكافية وأسواق التصدير, خاصة عند تنظيم هذه الزراعة والتخصص بإنتاج الشتول والزهور ونباتات الصالون. وقد حققت صالة الأمهات ربحاً وفيراً بعد أن وفرت قيمة الشتول التي كانت تدفع للصالات الأربع يقدر بحوالى820906 ل.س سنوياً . وقد بلغ معامل الريعية 139% ومعامل الربحية 37%, بينما زمن استعادة رأس المال 2.72 سنة. This research focuses on the current statues of  Horticulture Green plants in Syrian Coast. Despite that fact that the 2003 number of Green Houses (GHs) is 1115 on top of their precious profitability (both  within the local and foreign markets that utilities other states experiences), the Syrian Government has not yet provided the necessary support for this type of Coast cultivation. Cheflira plant has been chosen as an example of Horticulture Green Houses in view of the fact that it does not need very specialized expertise to cultivate as well as the growth period at which the planets will be soon ready for marketing. The comparative feasibility study for this plant consists of three growth periods. The first period is up to six months, the second is up to one year, and the third one is up to eighteen months. All of these have been grown in four 21000 squire meters green houses. Other green houses have planted with plants mothers. The results of this study have been encouraging. Farming for six months first period has yielded annual net revenues of 23414 Syrian pounds SPs, the second period has yielded 174674 SPs, and the third 140045 SPs. These figures are achievable if the availability of necessary services, sufficient experience and skills, and unrestricted foreign markets are secured. In particular, when this type of farming is regulated and when the production of cultivators, flowers, and saloon plants is specialized. The mothers green house has also achieved good profits because it saved the values of cultivators that otherwise would have been paid for the four green houses. The realized surplus has been 820906 SPs annually. Finally, the return factors is 139% and the profitability factor is 37% whereas the capital period is 2.72 year.